Peculiarites of benzene decomposition in cavitation fields - Znak, Zynovii; Sukhatskii, Yurii; Zin, Olha; Mnykh, Roman; Khomiak, Semen; Hrabarovska, Anastasiia (Видавництво Львівської політехніки, 2017)
It is proposed to carry out treatment of wastewaters, containing of aromatic compounds, in particular benzene, in cavitation fields. The results of studies of the cavitational decomposition of benzene under isothermal conditions (at temperatures 303, 313 and 323 K) are presented. The extremal characterof the dependence of the degree of decomposition of benzene from temperature with a minimum of 313 K is established. An abnormal appearance of the dependence is explained by possibility of occurrence of secondary processes , namely the formation of gas bubbles of nanometer sizes (babstons) and their clusters, which have high mechanical resistance and diffusivityy, and also on the basis of the kinetic theory of Frenkel's fluid.Recommendations for the implementation of the benzene decomposition process in cavitation fields are formulated on the basis of the results of experimental studies.
Keywords: cavitation fields; decomposition; benzene; ultrasonic magnetostrictive emitter; stationary treatment mode